2011
DOI: 10.1007/s00234-010-0826-y
|View full text |Cite
|
Sign up to set email alerts
|

Complication rates using balloon-expandable and self-expanding stents for the treatment of intracranial atherosclerotic stenoses

Abstract: Data of the INTRASTENT registry do not support the hypothesis that introduction of SES lowered the overall complication rate of intracranial stent procedures. There might be an advantage using self-expanding stents in vessel segments with important perforating arteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…30 However, recent publications have suggested that the complication rates with balloon-expandable stents are similar to those seen with self-expanding stents such as Wingspan. 31,32 Favorable rates of ipsilateral stroke beyond the 30-day period have also been reported for both angioplasty alone and for balloon-expandable stents. 23,26,27 However, these are all retrospective reports and the patients have not had the closer scrutiny of a randomized trial.…”
Section: T He Initial Results Of the Stenting And Aggressive Medicalmentioning
confidence: 99%
“…30 However, recent publications have suggested that the complication rates with balloon-expandable stents are similar to those seen with self-expanding stents such as Wingspan. 31,32 Favorable rates of ipsilateral stroke beyond the 30-day period have also been reported for both angioplasty alone and for balloon-expandable stents. 23,26,27 However, these are all retrospective reports and the patients have not had the closer scrutiny of a randomized trial.…”
Section: T He Initial Results Of the Stenting And Aggressive Medicalmentioning
confidence: 99%
“…Blasel et al 25 used BES in patients with >50% stenosis, with a 95% technical success rate and a 7.5% complication rate. Analysis of the multicentric INTRASTENT registry showed a rate of disabling stroke or death in 7.0% of the stent placements, with no clear significant differences between SES and BES (10.0% vs 4.5%, p=0.054) 26 27. The drawbacks of all these studies are lack of randomization, retrospective design, and a relatively small number of patients included.…”
Section: Discussionmentioning
confidence: 99%
“…This technique is faster and less prone to induce distal vessel perforation. In contrast, perforator occlusion appears to be more common in balloon-expanding than in self-expanding stents, and self-expanding stents may thus be advantageous in vessel segments with important perforating arteries [18,19]. Passage of the distal internal carotid artery with the more rigid balloon expanding stents can be difficult particularly in patients with a narrow and rigid siphon [19].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, perforator occlusion appears to be more common in balloon-expanding than in self-expanding stents, and self-expanding stents may thus be advantageous in vessel segments with important perforating arteries [18,19]. Passage of the distal internal carotid artery with the more rigid balloon expanding stents can be difficult particularly in patients with a narrow and rigid siphon [19]. These limitations of balloon expanding stents were at least in part resolved by the development of very flexible, balloon-mounted coronary stents, which are employed in off-label use in cerebrovascular interventions [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation